Effectivity of Extracorporeal Shock Wave Lithotripsy (ESWL) and Stenting vs. Stenting Only for Difficult Common Biliary Duct Stones: A Retrospective Analysis - Maulahela, Hasan; Rumagesan, Djahalia; Abdullah, Murdani; Makmun, Dadang; Renaldi, Kaka; Simadibrata, Marcellus; Shatri, Hamzah; Fauzi, Achmad; Tandan, Manu (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) alone may not be sufficient for treating difficult common bile duct stones. To address this challenge, several other modalities exist, including extracorporeal shock wave lithotripsy (ESWL) and biliary stent placement. This study aims to investigate the effectiveness of ESWL following biliary stent placement, in comparison to biliary stent placement alone , in the treatment of difficult common bile duct stones.Methods: A retrospective cohort study was conducted using medical record data from the Gastrointestinal Endoscopy Center Registry of Dr. Cipto Mangunkusumo General National Hospital. This study evaluated 126 subjects with difficult bile stones, who were divided into two groups: one group received biliary stent placement alone, while the other underwent extracorporeal shock wave lithotripsy (ESWL) following biliary stent placement. The effectiveness of each treatment was assessed based on the rate of complete clearance of bile stones.Results: Of the total participants, 72 underwent ESWL following biliary stent placement, while 54 received biliary stent placement alone. The rate of complete stone clearance was 69.1% in the ESWL group and 64.8% in the stent-only group. However, the addition of ESWL as an adjuvant therapy did not result in a statistically significant improvement (p = 0.703; 95% CI: 0.816–1.351). Normal body mass index was a factor that influences the effectiveness of ESWL after biliary stent placement (p = 0.002).Conclusion: The ESWL procedure as adjuvant therapy following biliary stent placement has the same level of effectiveness as biliary stent placement alone.